Edukasi Gizi Seimbang melalui Program “Isi Piring Sehat untuk Remaja Hebat” - Dwi Helynarti Syurandhari; Elyana Mafticha; Mukhammad Himawan Saputra (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2026)
Adolescent nutrition problems were associated with limited dietary diversity and insufficient understanding of balanced meal composition. This community service program aimed to improve orphanage adolescents’ knowledge of balanced nutrition through the “Healthy Plate for Great Adolescents” program. The activity was conducted at YPAY Al-Ikhlas Mojokerto in Tuesday, 05 May 2026 and involved 30 adolescents. The methods included interactive lectures, question-and-answer sessions, posters and slides, group games, a pre-test, a post-test, and healthy-behaviour commitments. Knowledge was measured using ten true-false statements and analysed descriptively. The mean score increased from 5.60±1.25 to 8.70±0.65, representing a 3.10-point improvement. The proportion of participants in the good-knowledge category increased from 10.0% to 100%. Twenty-seven participants (90.0%) correctly identified the complete components of a healthy plate, 26 participants (86.7%) provided examples of diverse foods, and all participants selected one healthy commitment. Simple communication, locally available food examples, visual media, and educational games encouraged active participation and improved comprehension. Orphanage administrators were advised to display the educational media in visible areas and provide periodic reinforcement to maintain knowledge and support the implementation of healthy commitments. The program demonstrated that contextual and participatory education can serve as a practical approach to improving nutrition literacy among adolescents living in orphanage settings